Rivaroxaban: Expanded Role in Cardiovascular Disease Management—A Literature Review. (8th January 2021) - Ajmal, Muhammad; Friedman, Jacob; Sipra, Qurat Ul Ain Riaz; Lassar, Tom
Abstract : Direct oral anticoagulants (DOACs) are widely used for the prevention of stroke in nonvalvular atrial fibrillation, treatment of deep venous thrombosis and pulmonary embolism, and as prophylaxis after hip and knee surgery after approval by the Food and Drug Administration. In the last decade, DOACs were studied for various indications; this review is focused on rivaroxaban, a factor Xa inhibitor, which is used in an expanded evidence-based fashion for coronary artery disease, peripheral artery disease, heart failure, malignancy, and prophylaxis of deep venous thrombosis in acute medical illnesses.